Trade, Inequality and Distribution-Neutral Fiscal Policy - An Elementary Framework - Sugata Marjit; Lei Yang (Center for Economic Studies and ifo Institute (CESifo), 2017)
Theoretical discussion on compensating mechanisms involving the Pareto criterion that address inequality rather than absolute welfare is non-existent in trade literature. In a simple HOS model we consider tax-transfer policies that keep the pre-trade degree of inequality unchanged between skilled and unskilled workers rather than the absolute income of the losing group. We discuss the problem of existence of such an inequality-neutral tax rate which generates a positive increment in the after tax skilled wage and unskilled wage. Such a mechanism exists and is independent of whether the tax is progressive or proportional. Thus the compensating mechanism that is available in this standard model is stronger than the conventional Pareto criterion.
Keywords: F11; J31; D63; H20; H23; 330; trade model; wage inequality; compensation mechanism; tax policy